Associating schizophrenia, long non-coding RNAs and neurostructural dynamics - Merelo, Veronica; Durand, Dante; Lescallette, Adam R.; Vrana, Kent E.; Hong, L. Elliot; Faghihi, Mohammad Ali; Bellon, Alfredo (Frontiers in Molecular Neuroscience, 2015)
Several lines of evidence indicate that schizophrenia has a strong genetic component. But the exact nature and functional role of this genetic component in the pathophysiology of this mental illness remains a mystery. Long non-coding RNAs (lncRNAs) are a recently discovered family of molecules that regulate gene transcription through a variety of means. Consequently, lncRNAs could help us bring together apparent unrelated findings in schizophrenia; namely, genomic deficiencies on one side and neuroimaging, as well as postmortem results on the other. In fact, the most consistent finding in schizophrenia is decreased brain size together with enlarged ventricles. This anomaly appears to originate from shorter and less ramified dendrites and axons. But a decrease in neuronal arborizations cannot explain the complex pathophysiology of this psychotic disorder; however, dynamic changes in neuronal structure present throughout life could. It is well recognized that the structure of developing neurons is extremely plastic. This structural plasticity was thought to stop with brain development. However, breakthrough discoveries have shown that neuronal structure retains some degree of plasticity throughout life. What the neuroscientific field is still trying to understand is how these dynamic changes are regulated and lncRNAs represent promising candidates to fill this knowledge gap. Here, we present evidence that associates specific lncRNAs with schizophrenia. We then discuss the potential role of lncRNAs in neurostructural dynamics. Finally, we explain how dynamic neurostructural modifications present throughout life could, in theory, reconcile apparent unrelated findings in schizophrenia.